The prevalence of accessory renal arteries in sudanese population in Khartoum State: a cross-sectional CT study from 2017 to 2020 - Safaa. Mohammed; Eltayeb. AbdAlla; Amal. Elhag; Abdelmoniem. El-Mardi (BMC Nephrology, 2024)
Abstract Background Renal artery variations are clinically significant due to their implications for surgical procedures and renal function. However, data on these variations in Sudanese populations are limited. This study aimed to determine the prevalence and characteristics of renal artery variations in a Sudanese population. Methods A cross-sectional retrospective study was conducted in Khartoum state from October 2017 to October 2020. A total of 400 Sudanese participants who underwent abdominal CT scans were included. Data on demographic characteristics, kidney measurements, and renal vasculature were collected and analyzed using descriptive statistics and inferential tests. Results The mean age of participants was 46.7 ± 18 years, with a nearly equal gender distribution. Overall, renal artery variations were present in 11% of participants, with accessory renal arteries observed in 6% of the study population. Among those with accessory vessels, 50% were on the right side, 29.2% on the left, and 20.8% bilateral, distributed across hilar 29.2%, lower polar 29.2%, and upper polar 41.7% regions. No significant associations were found between accessory renal arteries and age or gender (p-value > 0.05). However, participants with accessory renal arteries exhibited significantly narrower width 5.0 ± 1.4 than those with no with accessory renal arteries 5.8 ± 1.1 (p-value 0.002) Early dividing renal arteries were found in 5% of participants, with nearly half being bilateral. No significant associations were found between the presence of early dividing renal arteries and demographic or renal measurements (p-value > 0.05). Conclusion This study provides valuable insights into the prevalence and characteristics of renal artery variations in a Sudanese population. The findings contribute to our understanding of renal anatomy in this demographic and can inform clinical practice and surgical planning, particularly in renal transplantation and other renal procedures.